2016
DOI: 10.4103/1305-7456.195173
|View full text |Cite
|
Sign up to set email alerts
|

Dental prosthetic status and treatment needs of adult population in Jizan, Saudi Arabia: A survey report

Abstract: Objectives:The study aimed to evaluate and compare the dental prosthetic status and treatment needs of adult population in Jizan, Saudi Arabia, in relation to the age.Materials and Methods:A total of 1779 people aged 35–74 years from 4 survey areas (Hay al matar, Mahata khams, Dara ut tawhid, and Suq ad dakhili) selected through convenient sampling, around Jizan University, were surveyed, using the WHO survey criteria, 1997.Statistical Analysis:Number and percentages were calculated, and univariate analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 6 publications
1
20
1
4
Order By: Relevance
“…The prevalence of tooth loss and the need for prosthetic treatment are high both in Brazil and worldwide [1, 2] and affect the well-being of individuals and the population [3]. To improve oral health-related quality of life, rehabilitation with removable or fixed prostheses is indicated to reestablish masticatory and aesthetic functions and to minimize the consequences of tooth loss and edentulism [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of tooth loss and the need for prosthetic treatment are high both in Brazil and worldwide [1, 2] and affect the well-being of individuals and the population [3]. To improve oral health-related quality of life, rehabilitation with removable or fixed prostheses is indicated to reestablish masticatory and aesthetic functions and to minimize the consequences of tooth loss and edentulism [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the findings of Myanmar adults and also among the adults of Saudi Arabia. 12,13 This could be due to lack of awareness and availability of oral health services along with the higher expenses associated with the treatment of oral diseases. Collectively leading to accumulation of oral diseases resulting in need for tooth rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, a prevalence ranging from 33.2 to 81.2% has been observed, depending on the population group studied. [13][14][15][16] Although there have been substantial improvements in the oral health of populations in several countries, different dental problems persist worldwide. The burden of oral diseases is particularly high in socioeconomically disadvantaged populations, which can be observed in both developing and developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…14 In Saudi Arabia, Peeran et al performed a study in adults aged 35-74 years and observed that about 56% of the participants had dental prosthetic needs. 15 On the other hand, in Thailand, prosthetic needs reach 60% in subjects aged 60-75 years. 16 The determination of prosthetic needs in Mexico is a little-explored subject so the objective of the present study was to determine the influence of various indicators of the socioeconomic position on prosthetic needs in elderly Mexicans of 60 years and over.…”
mentioning
confidence: 99%